ANALISIS INFORMASI KEUANGAN KOPERASI SYARIAH NURI (KSN) JAWA TIMUR SEBAGAI ALAT PENGAMBILAN KEPUTUSAN INVESTASI - Devi Lestari Pramita Putri; Wahyu Maulana (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2019)
Nowadays, economic conditions in Indonesia are unstable, with the result that it is needed to look forthe information from certain or credible sources. Especially in financial information because of that, itis very influential to those who play an important role in policymakers. Besides, the precise financialinformation is also needed by the investors and creditors who are used as a basis for consideration tomake profitable investments or vice versa. The objective of this study is to find out the financialinformation as an investment decision-making tool and to find out the level of health of cooperatives inthe financial sector as financial information to investors and creditors. Then, the object of this study isKoperasi Syariah Nuri in East Java. This study employed descriptive quantitative research. Thesampling technique is purposive sampling. The data sample used is in the form of financial statementsfrom 2015 to 2017. Based on the data analysis, the results show us that: capital ratio in healthycriteria, cash ratio in liquid criteria, ROA insufficient criteria, ROE insufficient criteria, Fewercriteria generated by the service operational independence ratio.